2ef+3ef=

Simple and best practice solution for 2ef+3ef= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2ef+3ef= equation:


Simplifying
2ef + 3ef = 0

Combine like terms: 2ef + 3ef = 5ef
5ef = 0

Solving
5ef = 0

Solving for variable 'e'.

Move all terms containing e to the left, all other terms to the right.

Divide each side by '5'.
ef = 0

Simplifying
ef = 0

The solution to this equation could not be determined.

See similar equations:

| 5x+(7x+2)+(7x+6)= | | 2m^2=-4m+6m | | 7q-4q+8= | | 3b^4+18b^3+27b^2= | | log(2x-4)=-0.7 | | 2x+5=-2x-8-x | | -40=8(x-3)-3/2(6x-16 | | .16x+1500=x | | (X)2+(Y-1)2=81 | | 0=16t^2+96t-140 | | 5k^2+20k+100=0 | | 5k^2+20k+100=100 | | (x-5)-(x-12)= | | (t/2-20)/4=4 | | 5*7x^2y=175 | | 21/15=3x-2/5 | | 12/3x=36/63 | | 5m(4m+11)= | | Y=(8-x)^1/2 | | 4x=x+180 | | 13.2x+x^2-1246=0 | | 34x-9x+12=20+3x | | 4t-6h+8t-12h+4= | | 1/2(-0.86) | | 35=-29+(n-1)(-7) | | 13.2x+x^2-1296=0 | | 5u+16=61 | | 35=-29+(n-1)-7 | | 7=2v-15 | | (n-1)(n-2)(n-3)=720 | | 4(2.5-6.0)= | | 50x+x^2-8400=0 |

Equations solver categories